Audit Judgement In Task Complexity, Self Efficacy, and Auditor Professional Skepticism - Aqsha, Muhammad; Masruddin; Ansar, Muhammad; Jurana; Tenripada; Bawias, Hizkia Hazael Bezaliel (CV. Muris Global Education, 2025)
The presentation of quality audit reports does not necessarily occur without problems, including in the provision of audit judgments by auditors who are faced with task complexity and auditor confidence in their abilities including skepticism. The study was conducted with the aim of examining the impact of task complexity, self-efficacy and professional skepticism of auditors on policy making in audit judgement with internal auditors at the regional inspectorate of Central Sulawesi. A total of 32 respondents who met the criteria in determining the sample using purposive sampling with a survey approach. The results showed that the effect caused in giving audit judgments on task complexity, self efficacy, and professional skepticism of internal auditors was significant. The results of the study can be a reference for further research in developing audit judgment and can be material in developing the ability of internal auditors to convince themselves of the decisions given in the audit results